Cuba Libre : A Novel - Leonard, Elmore (New York A Dell Book, 1999)
A novel on the Spanish-American War featuring adventurer Ben Tyler, an Arizona horse dealer. Just as he arrives in Cuba with a shipment of guns and horses, war breaks out. To get his money, he is sucked into fighting between Spain, the U.S. and Cuban revolutionaries seeking independence from both.
Keywords: Cuba -- Spanish-American War (1898) -- Americans -- Americans--Travel